Analisis Faktor yang Mempengaruhi Indeks Pembangunan Manusia (IPM) di Kabupaten Tuban - Setya Surya Wardhana; Riko Setya Wijaya; Putra Perdana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human development is an important indicator in assessing the success of a region's development, which is reflected through the Human Development Index (HDI). In 2023, Tuban Regency ranked 11th in terms of the highest GRDP per capita in East Java with a value of Rp41,018 thousand, but the achievement of the Human Development Index (HDI) was still low, namely 70.34% and ranked 27th. This study aims to analyze the factors that influence the Human Development Index (HDI) in Tuban Regency. This study uses a quantitative descriptive method with time series data for 15 years (2009–2023) with the help of SPSS version 27. The analysis was carried out using multiple linear regression and classical assumption tests. The results showed that the variables GRDP per capita, Life Expectancy, and Level of Disturbance have a significant effect on the Human Development Index (HDI). Meanwhile, Expected Years of Schooling and Poverty Level did not show a significant effect. These findings empirically state that improving the quality of health, people's purchasing power, and reducing poverty have a very important and strategic role in encouraging the acceleration of human development in Tuban Regency in a comprehensive and sustainable manner.